Molecular aspects of mucin biosynthesis and mucus formation in the bovine cervix during the periestrous period - Pluta, Katarzyna; McGettigan, Paul A; Reid, Colm J; Browne, John A; Irwin, Jane A; Tharmalingam, Tharmala; Corfield, Anthony; Baird, Alan; Loftus, Brendan J; Evans, Alexander C O; Carrington, Stephen D (Physiological genomics, 2012)
Mucus within the cervical canal represents a hormonally regulated barrier that reconciles the need to exclude the vaginal microflora from the uterus during progesterone dominance, while permitting sperm transport at estrus. Its characteristics change during the estrous cycle to facilitate these competing functional requirements. Hydrated mucin glycoproteins synthesized by the endocervical epithelium form the molecular scaffold of this mucus. This study uses the bovine cervix as a model to examine functional groups of genes related to mucin biosynthesis and mucus production over the periestrous period when functional changes in cervical barrier function are most prominent. Cervical tissue samples were collected from 30 estrus synchronized beef heifers. Animals were slaughtered in groups starting 12 h after the withdrawal of intravaginal progesterone releasing devices (controlled internal drug releases) until 7 days postonset of estrus (luteal phase). Subsequent groupings represented proestrus, early estrus, late estrus, metestrus, and finally the early luteal phase. Tissues were submitted to next generation RNA-seq transcriptome analysis. We identified 114 genes associated with biosynthesis and intracellular transport of mucins, and postsecretory modifications of cervical; 53 of these genes showed at least a twofold change in one or more experimental group in relation to onset of estrus, and the differences between groups were significant (P < 0.05). The majority of these genes showed the greatest alteration in their expression in the 48 h postestrus and luteal phase groups.